In Search of Social justice-informed Services: A Research Agenda for the Study of Resistance to Neo-managerialism. (8th July 2022) - Timor-Shlevin, Shachar; Hermans, Koen; Roose, Rudi
Abstract: One of the main characteristics of social work is the fundamental tension between the profession's conservative and critical rationales. In the last three decades, this tension has informed the development of critical resistance to the deprofessionalisation effects of neo-managerial rationality, which establishes cost reduction and fiscal accountability as the basis for professional practice. However, the theoretical conceptualisation of such critical resistance is caught between minor and major operations, both of which are considered insufficient. Addressing this gap, this article builds on the theoretical framework of radical incrementalism to develop a research agenda for the future study of resistance processes, which we conceptualise as operating in the middle range of a power exertion scale, between minor and major forms of operation. We portray the operation of resistance in the middle range of such a power exertion scale and offer a research agenda that includes relevant research directions and methodological considerations. In this way, the article suggests new ways of understanding, conceptualising and operating resistance to enable further development of the social justice-informed professionalisation of social work. Abstract : This article offers a research agenda for studying processes that resist the current articulation of social work policies and practices in social services. In the last three decades, neoliberal ideas known as neo-managerial reforms have been implemented in social services to promote fiscal accountability. Whilst these reforms aim to increase efficiency, they are considered to decrease the responsiveness and professional operation of social workers and social services, especially in work with marginalised groups. Thus, a central theme in social work literature is the search for ways in which to resist neo-managerial effects to promote social justice in terms of expanding the inclusiveness and responsiveness of social services. Yet, these efforts seem to be articulated as either minor efforts that remain mainly local and do not challenge the current order or major ones that remain mainly theoretical. In this article, we use the theoretical idea of radical incrementalism to offer a new direction for researching contextualised and internal ways of developing resistance to neo-managerial effects. We conceptualise resistance as operating on a scale of power exertion and suggest relevant research questions and methodological considerations for conducting research on resistance processes in the middle range of the power exertion scale.